Comparison of Physical Activity Levels in Rheumatic Diseases (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2017)
Acar M et al. Comparison of Physical Activity Levels in Rheumatic Diseases. Akt Rheumatol 2017; 42 (04): 329–335